(untitled) (The Review of Diabetic Studies, 2023)
OBJECTIVES: Limited data are available on metformin therapy in gestational diabetes. The aim of the study was to compare maternal and neonatal outcomes in patients with gestational diabetes mellitus (GDM) treated with metformin with those treated with insulin, or diet alone. STUDY DESIGN AND METHODS: We conducted a retrospective study that included 45 GDM women treated with metformin, 45 women treated with insulin and 83 women with no pharmacological treatment. Subjects were matched for pre-pregnancy body mass index (BMI) and age. RESULTS: There were no differences between the metformin-treated group and the other two groups in terms of maternal outcomes (total weight gain during pregnancy or after the diagnosis of GDM, pre-pregnancy hypertension, pregnancy induced hypertension, pre-eclampsia etc.). In the diagnostic 2- hour oral glucose tolerance test, glucose values were slightly, but significantly, higher in the insulin group than in the metformin group (p < 0.003). Eighteen percent of mothers treated with metformin needed supplementary insulin therapy. No differences between the metformin-treated group and the other two groups (insulin, diet only) were observed in relation to mean birth weights, prevalence of macrosomia, or gestational weeks at delivery. The incidence of neonatal hypoglycemia was higher in the insulin group than in the metformin group (p = 0.03). There were no differences between the groups in other neonatal outcomes (small for gestational age, Apgar scores, umbilical artery pH or base excess, etc.). CONCLUSION: These retrospective data suggest that metformin is effective in controlling gestational diabetes and is not associated with a higher risk of maternal or neonatal complications compared with insulin.